Implementation of the Coaching Clinic Method for Phase F Vocational School Students Majoring in Accounting to Improve Industry Competence - Sohidin Sohidin; Binti Muchsini; Elvia Ivad; Siswandari Siswandari; Asri Diah Susanti (Economic Education Analysis Journal, 2026)
Industrial competence remains a persistent challenge in vocational accounting education, particularly in Phase F where alignment between school-based learning and workplace expectations is often weak. Prior studies have largely emphasized technical instruction, offering limited empirical evidence on coaching-oriented pedagogies grounded in experiential and competency-based learning. Addressing this gap, this study investigates the effect of the Coaching Clinic method a practice-oriented, feedback-intensive learning approach informed by experiential learning and workplace learning theory on students’ industrial competence, conceptualized as the integration of technical accounting proficiency, problem-solving ability, professional communication, and work discipline. A quasi-experimental Non-Equivalent Control Group Design was employed involving two Grade 11 accounting classes at a public vocational school in Indonesia (N=approximately two intact classes). Comparative analysis using N-Gain and independent t-tests indicates that the experimental group demonstrated substantially greater competence development than the control group, suggesting meaningful pedagogical impact beyond statistical significance. However, findings should be interpreted within the contextual limits of a single institutional setting. This study contributes empirical evidence on coaching-based vocational pedagogy and highlights the Coaching Clinic method as a structured bridge between classroom instruction and industry-oriented competence formation, offering implications for strengthening practice-based vocational curriculum and school–industry learning integration.